(untitled) - World Bank in Vietnam (WB) (Hà Nội, 2003)
The Rural Finance Project supports several key components of the IDA's country assistance strategy, which are: 1) assist transition to a market economy; 2) strengthen the rural finance system through finance targeted to agriculture and small and medium enterprises in rural areas, accompanied by technical assistance; and 3) reduction of poverty through promoting growth and enabling the poor to respond to opportunities to improve their welfare. The project will also assist Viet Nam in its efforts to improve living conditions in the rural areas through: 1) encouraging private sector investments; 2) strengthening the banking system's capacity to finance private sector investments; and 3) increasing access of the rural poor to financial services. The project will consist of the following components: 1) rural development fund; 2) fund for the rural poor; 3) equipment; 4) vehicles; 5) training; and 6) technical assistance.
Keywords: Technical assistance,Hỗ trợ kỹ thuật,Rural development,Phát triển nông thôn